2021
DOI: 10.1371/journal.pone.0254129
|View full text |Cite
|
Sign up to set email alerts
|

High rate of HSV-1 reactivation in invasively ventilated COVID-19 patients: Immunological findings

Abstract: SARS-CoV-2 infection can lead to severe acute respiratory distress syndrome with the need of invasive ventilation. Pulmonary herpes simplex-1 (HSV-1) reactivation in invasively ventilated patients is a known phenomenon. To date very little is known about the frequency and the predisposing factors of HSV-1 reactivation in COVID-19. Therefore, we evaluated our cohort of invasively ventilated COVID-19 patients with severe pneumonia for HSV-1 in respiratory specimens and combined these results with functional immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 28 publications
1
41
1
2
Order By: Relevance
“…HSV reactivation has been more often described in critically-ill COVID-19 patients, despite its impact on hospital mortality is still controversial [ 22 , 23 , 42 ]. Moreover, HSV reactivation was associated to the length of stay on ICU and mechanical ventilation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSV reactivation has been more often described in critically-ill COVID-19 patients, despite its impact on hospital mortality is still controversial [ 22 , 23 , 42 ]. Moreover, HSV reactivation was associated to the length of stay on ICU and mechanical ventilation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few cases of CMV reactivation in the setting of severe COVID-19 have been reported [ 16 19 ]. Intriguingly, also reactivation of EBV and Herpes simplex virus (HSV) have been described [ 20 23 ], indicating that these latent herpesvirus infections may further contribute to the development of severe COVID-19. However, it remains to elucidate whether herpesvirus reactivations are a direct consequence of SARS-CoV-2 infections or of the treatments related to COVID-19 (for example steroids), and whether they affect the same category of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A possible speculative hypothesis to be further explored may be the lung inhalation after oropharyngeal reactivation, without significant pulmonary damage [15]. Regarding mortality, it should be considered that the available literature on the prognostic impact of HSV-1 reactivation in non-COVID-19 critically ill populations (which also remains controversial) may be not extrapolated directly to COVID-19 patients, owing to the possibly different immunological background [6,[15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients with coronavirus disease 2019 (COVID-19) pneumonia requiring invasive mechanical ventilation are at risk of developing bacterial, fungal, and viral superinfections [1][2][3][4]. Reactivation of herpes simplex virus type 1 (HSV-1) has been described in intubated critically ill patients with coronavirus disease 2019 (COVID- 19) pneumonia [2,3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Reactivation of latent HSV and CMV infections has been reported among COVID-19 patients [ 138 ]. Seeßle et al [ 139 ] found a high rate of HSV-1 reactivation (83.3%, 15 out of 18 patients) in invasively ventilated COVID-19 patients. Encephalitis due to HSV-1 was reported in a 73-year-old woman who suspected to prior COVID-19 infection [ 140 ].…”
Section: Viral Infectionsmentioning
confidence: 99%